Comparative analysis of protein structure of common Hb Q variants - Yadav Amit (Wolters Kluwer Medknow Publications, 2010)
Context: Hemoglobin (Hb) Q variant is a group of hemoglobinopathies prevalent in south, south-east and western Asia. The primary structure of all of these molecules is well known. However, very little is known about the secondary and tertiary structures of these molecules. Therefore, a study of their secondary and tertiary structures is needed. Aim: The study was aimed at investigating the secondary and tertiary structures of common Hb Q variants using bioinformatics tool. Settings and Design: The secondary and tertiary structures of common Hb Q variants were evaluated using NNPREDICT server and CPHmodels 2.0 server, respectively. Materials and Methods: Amino acid sequence of alpha globin chain was searched using ExPASY and was used for further mutation to Hb Q variants. The derived sequences were further analyzed using NNPREDICT server and CPHmodels 2.0 server to calculate their secondary and tertiary structures, respectively. These were then compared and any differences noted. Results: It was observed that there is no difference between the predicted secondary structures of normal alpha globin and Hb Q-India. Hb Q-Iran carries an extra helix while Hb Q-Thailand carries two extra helices. The results of tertiary structure prediction also support these findings. Conclusions: Differences in secondary and tertiary structure of various Hb Q variants have been observed in the present study. The study provides valuable data for better understanding of these uncommon hemoglobinopathies.